About the provability of the Kotzig's hypothesis - Maliaukienė, Livija (Lietuvos matematikos rinkinys, 2004)
In the paper Kotzig's hypothesis are investigated and turning its into theorem from the point of views of history are presented.
Keywords: graph theory; Kotzig's hypothesis